Influence of cement type, air-entrained admixture and hydration stabilizing admixture on mortars’ setting time - Antoniazzi,Juliana Pippi (2021)
ABSTRACT: Ready mix mortar is a ready to use mixture that uses hydration stabilizing (HSA) and air-entrained (AEA) admixtures in its composition, which modify its properties, especially the setting times. HSA extends the setting time of mortars for a long period, while AEA promotes a greater workability to the mixture. The study determined the temperature of the mortars with the evaluation of the setting times obtained by a semi-adiabatic calorimeter. Two types of cement (CPII-F-40 e CPII-Z-32) and varied contents of HSA (0.0%, 0.6% e 0.9%) and AEA (0.0%, 0.2% e 0.4%) were used. The results showed that the use of HSA decreased the amplitude of the temperature peaks and increased the setting times with cement CPII-Z-32 in relation to cement CPII-F-40. The setting time of the mortars was influenced by the type of cement used and by the contents of the admixtures.